Discharge and corrosion behaviour of Mg-Li-Al-Ce-Y-Zn alloy as the anode for Mg-air battery. (November 2016) - Wang, Naiguang; Wang, Richu; Feng, Yan; Xiong, Wenhui; Zhang, Junchang; Deng, Min
Highlights: We investigate the discharge behaviour of Mg-Li-Al-Ce-Y-Zn alloy. We include pure Mg, AZ31, and Mg-Li-Al-Ce-Y alloy for comparison. We evaluate the performance of Mg-air batteries with the above four anodes. We analyze the dissolution mechanism of Mg-Li-Al-Ce-Y-Zn alloy during discharge. Abstract: The discharge and corrosion behaviour of Mg-Li-Al-Ce-Y-Zn alloy in 3.5 wt.% NaCl solution is investigated by electrochemical techniques, and compared with that of pure magnesium, AZ31, and Mg-Li-Al-Ce-Y alloys. The results indicate that Mg-Li-Al-Ce-Y-Zn exhibits desirable performance in half-cell tests and battery discharge. The peak power density of the Mg-air battery with Mg-Li-Al-Ce-Y-Zn anode is comparable with that of Mg-H2 O2 semi-fuel battery. Its anodic efficiency at 10 mA cm −2 reaches (60.6 ± 0.2)%, which is significantly higher than that of the state-of-the-art AP65 magnesium alloy. Moreover, the dissolution mechanism of Mg-Li-Al-Ce-Y-Zn is also characterized based on electrochemical response and microstructure observation.